A atuação das organizações sociais de saúde nos hospitais de campanha dentro da política pública de saúde: um estudo no caso do estado de Goiás no contexto da pandemia da covid-19 - Valle, Anna Carolina Miranda Bastos do (2023)
This research has the scope of investigating public hospital health policy based on management contracts with social health organizations in Goiás, focusing on the role of control bodies in monitoring and evaluating this public policy in the context of the covid-19 pandemic. 19. The universe of study is delimited in the analysis of the state hospital management within the scope of the Department of Health of the State of Goiás. The sample selected for the investigation is equivalent to the emergency management contracts carried out with social organizations for the management of field hospitals for the care of patients with covid-19. The theoretical framework for organizing this research is the Law and Public Policy Approach and the methodology adopted was bibliographic research and documentary research. The analysis method is presented through the deductive method. An analysis of federal legislation, national jurisprudence and state legislation was carried out to, together with the construction of the reference framework for public hospital management policy through social organizations in Goiás, raise the necessary legal subsidies to carry out the diagnosis. This was carried out in 3 (three) stages through qualitative research, of a descriptive nature, using the documentary approach. The first stage analyzes the scenario of the covid-19 pandemic in the State of Goiás and the related legislation. The second stage includes the diagnosis of SES' performance in the process of monitoring and evaluating management contracts during the covid-19 pandemic through the analysis of the items: (i) qualification; (ii) general information; (iii) financial and (iv) accountability. The third stage includes the analysis of the performance of the State Comptroller General (CGE), the Goiás Agency for Regulation, Control and Inspection of Public Services (AGR), the State Court of Auditors (TCE), the Legislative Assembly (ALEGO), of the Excellence Council of Public Hospital Units Managed by Social Health Organizations and the State Health Council in monitoring and evaluating the management contracts signed with OSS in Goiás for field hospitals in the years 2020 and 2021. At the end, it is necessary to structure the governance of the aforementioned public policy in order to have a coordinated action between the actors that compose the legal-institutional design, the broad evaluation of the public policy and not only the punctual monitoring of the management contracts, greater popular participation and social control, reformulation of procedures to avoid payments for estimates, verification of integrity programs, active internal control, external control of public policy and the realization of the fundamental social right of health for the population.